Switchers : how smart professionals change careers-- and seize success - Graham, Dawn ([Nashville, USA] : HarperCollins Leadership, 2018)
This book shows you how to land your dream position. Written by a top career coach, licensed psychologist, former recruiter, and a switcher herself, this book explains how to break past obstacles, maintain your motivation, and launch a better, more rewarding career
Keywords: Career changes; Job hunting; Success